An Extremely Rare Cause of Restrictive Lung Disease: Intrapulmonary Mature Teratoma - Kevin J. Karlic; Andrew C. Chang; John Z. Ayanian; Allison L. Ruff (Annals of Internal Medicine: Clinical Cases)
Intrapulmonary mature teratomas are extremely rare, benign neoplasms that arise from the lung. In this case, we present a 40-year-old man with a 1.5-year history of mild exertional dyspnea during physical exercise. Pulmonary function tests revealed restrictive lung disease and computed tomography (CT) of the chest showed a left mediastinal mass consistent with a mature teratoma obstructing the left ventricle and right ventricular outflow tract. Surgical resection revealed that the mass originated from the left upper lobe of the lung, while surgical pathology confirmed the diagnosis of intrapulmonary mature teratoma. Although commonly asymptomatic, intrapulmonary mature teratomas are a rare cause of mildly symptomatic restrictive lung disease.